LITERATURE REVIEW: PENGARUH TERAPI MUSIK KLASIK TERHADAP PENURUNAN TANDA DAN GEJALA SERTA KEMAMPUAN MENGONTROL PADA PASIEN HALUSINASI : LITERATURE REVIEW: THE EFFECT OF CLASSICAL MUSIC THERAPY ON THE REDUCTION OF SIGNS AND SYMPTOMS AS WELL AS THE ABILITY TO CONTROL IN PATIENTS WITH HALLUCINATIONS - Syifa Fauziah; Nyumirah, Sri (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2025)
Background: Hallucinations are a common symptom in schizophrenia patients which if left untreated can harm themselves and others. Hallucinations are a mental disorder that affects more than 21 million people worldwide and it is estimated that up to 400 thousand people experience hallucinations in Indonesia. Classical music therapy as a form of complementary therapy that has been proven effective in reducing signs and symptoms and increasing patients ability to control them. Classical music works by creating a relaxing effect and stimulating positive hormones that help emotional stability, therefore, this therapy is a effective non-pharmacological alternative in managing hallucination symptoms. Objective: To determine the effect of classical music on reducing signs and symptoms and the ability to control in hallucination patients. Method: The search strategy was carried out through Google Scholar with journals published in 2020-2025. The research method used was a literature review based on analysis and synthesis of previously existing studies with a total of five articles published in 2020-2025. Results: Literature review shows that classical music therapy has an effect on reducing signs and symptoms and the ability to control in hallucinatory patients. Conclusion: Classical music therapy can be used as a complementary therapy to reduce signs and symptoms and increase the ability to control in hallucinatory patients.